Method for producing aluminum-resin composite, and surface treatment agent
Through a two-step surface treatment method, alkaline and acidic surface treatment agents are used to treat aluminum components, which solves the problem of difficulty in maintaining the joint strength of aluminum-resin composites in the existing technology, and achieves high joint strength and continuous manufacturing effects.
Patent Information
- Application Number
- CN202380043354.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-04-05
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, when manufacturing an aluminum-resin composite, the bonding strength is difficult to maintain a high bonding strength, and frequent exchange of liquids is required to maintain a sufficiently high bonding strength.
A two-step surface treatment method is adopted, first using an alkaline surface treatment agent containing an alkali source, amphoteric metal ions, oxidants and sulfur compounds to treat aluminum components, followed by an acidic surface treatment agent containing halogen ions, aluminum ions, ammonium ions and acids. aluminum component, and finally the resin composition is bonded to the surface of the treated aluminum component.
It realizes the continuous production of aluminum-resin composites with high joint strength, avoids the problem of frequent liquid exchange, and improves the adhesion and joint strength of the composite.
Smart Images

Figure BDA0005156395970000151 
Figure BDA0005156395970000161 
Figure BDA0005156395970000181
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing an aluminum-resin composite and a surface treatment agent used in the production method. Background Art
[0002] A technology for manufacturing an aluminum-resin composite, which is a composite composed of a component made of aluminum and a resin, has been developed in a wide range of industrial fields, mainly in the electrical, electronic, and automotive fields. As a method for manufacturing a composite composed of a component made of aluminum (hereinafter referred to as an aluminum component) and a resin used in the composite, there is a method of bonding the surface of the aluminum component and the resin using an adhesive. However, depending on the purpose of use of the composite, the heat resistance of the adhesive may become an issue.
[0003] Therefore, a technique has been developed in which the surface of an aluminum member is chemically treated with a surface treatment agent such as an etchant without using a bonding agent, and a resin composition is bonded to the treated surface to produce an aluminum-resin composite.
[0004] When an aluminum member and a resin composition are bonded by chemical treatment, bonding strength becomes an issue, and therefore, there is a demand for improvement in technology for increasing bonding strength by chemical treatment.
[0005] This technology is described in Patent Documents 1 and 2 listed below, for example.
[0006] Patent Document 1 describes that after roughening the surface of an aluminum member with an alkaline surface treatment agent containing an alkali source such as NaOH or KOH, the surface is further treated with an acidic solution such as an aqueous nitric acid solution, an aqueous sulfuric acid solution, or an aqueous solution containing sulfuric acid and hydrogen peroxide.
[0007] Patent Document 2 describes that after an aluminum member is treated with an alkaline etching solution containing a sulfur compound, the roughened surface is further treated with an acidic etching solution containing at least one of a second iron ion and a second copper ion and an acid.
[0008] Patent Documents 1 and 2 describe that the adhesion between aluminum and a resin composition can be improved by further treating with an acidic solution after treating with an alkaline solution.
[0009] However, in the methods described in Patent Documents 1 and 2, the etching rate may decrease and the performance of the surface treatment agent may decrease during continuous treatment, and the bonding strength of the resulting composite may be difficult to maintain high. In addition, there is a problem that the liquids must be frequently replaced in order to maintain sufficiently high bonding strength.
[0010] [Prior art literature]
[0011] [Patent Document]
[0012] Patent Document 1: Japanese Patent Application Publication No. 2011-195949.
[0013] Patent Document 2: Japanese Patent Application Publication No. 2013-052671. Summary of the invention
[0014] [Problems to be solved by the invention]
[0015] The present invention has been developed in view of the above-mentioned problems of the prior art, and an object of the present invention is to provide a method for continuously producing an aluminum-resin composite having a high bonding strength, and a surface treatment agent that can be used in the method.
[0016] [Methods to solve the problem]
[0017] The present invention includes the following steps: a first surface treatment step, in which the surface of the aluminum component is brought into contact with an alkaline surface treatment agent, wherein the alkaline surface treatment agent contains an alkali source, amphoteric metal ions, an oxidant, and a sulfur compound; a second surface treatment step, in which the surface of the aluminum component after the first surface treatment step is brought into contact with an acidic surface treatment agent, wherein the acidic surface treatment agent contains halogen ions, aluminum ions, ammonium ions, and an acid, and contains the acid at an acid concentration of 3.0 mass % to 4.9 mass % and contains the aluminum ions at a concentration of 0.2 mass % to 3.8 mass %; and a bonding step, in which a resin composition is bonded to the surface of the aluminum component after the second surface treatment step.
[0018] In the present invention, the acidic surface treatment agent may contain an amine compound.
[0019] In the present invention, the acidic surface treatment agent may contain 0.05 mass % to 5.0 mass % of the amine compound.
[0020] In the present invention, the acidic surface treatment agent may contain the ammonium ion in an amount of 0.033 mass % to 3.37 mass %.
[0021] In the present invention, the halogen ion may be at least one selected from the group consisting of chloride ion, bromide ion, and fluoride ion.
[0022] In the present invention, the acidic surface treatment agent may contain hydrochloric acid, aluminum chloride, and ammonium chloride.
[0023] In the present invention, the sulfur compound of the alkaline surface treatment agent may be one or more selected from thiosulfate ions and sulfur compounds having 1 to 7 carbon atoms.
[0024] The present invention may further include the following step: a washing step of ultrasonically washing the surface of the aluminum member after the second surface treatment step.
[0025] In the present invention, in the second surface treatment step, the acid concentration of the acidic surface treatment agent may be maintained in a range of 3.0 mass % to 4.9 mass %.
[0026] In the present invention, in the second surface treatment step, the aluminum ion concentration of the acidic surface treatment agent may be maintained in a range of 0.2 mass % to 3.8 mass %.
[0027] The surface of the aluminum member after the second surface treatment step has an arithmetic mean roughness (Ra) of 0.5 μm to 3.0 μm, and a ten-point average roughness (Rz) of 8 μm to 30 μm.
[0028] The surface treatment agent of the present invention is an acidic solution, which contains halogen ions, an acid with an acid concentration of 3.0 mass % to 4.9 mass %, aluminum ions of 0.2 mass % to 3.8 mass %, and ammonium ions of 0.033 mass % to 3.37 mass %, and chemically etches by contacting with the surface of the aluminum component, thereby roughening the aluminum.
[0029] In the surface treatment agent of the present invention, the acidic solution may contain 0.05 mass % to 5.0 mass % of an amine compound.
[0030] In the surface treatment agent of the present invention, the halogen ion may be at least one selected from the group consisting of chloride ion, bromide ion, and fluoride ion.
[0031] In the surface treatment agent of the present invention, the acidic solution may contain hydrochloric acid, aluminum chloride, and ammonium chloride.
[0032] [Effects of the invention]
[0033] According to the present invention, a method for producing an aluminum-resin composite having high bonding strength can be continuously produced, and a surface treatment agent that can be used in the method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a schematic perspective view of a test aluminum-resin composite used in this example.
[0035] Figure 2 Part (a) is Figure 1 A top view of the experimental aluminum-resin composite, Figure 2 Part (b) is for Figure 1 Side view of the experimental aluminum-resin composite.
[0036] Figure 3 This is a graph showing changes in aluminum concentration during cycle tests in Examples.
[0037] Figure 4 This is a graph showing changes in various properties in the cycle test of Examples.
[0038] Figure 5This is a graph showing changes in various properties in the cycle test of Examples.
[0039] Figure 6 This is a graph showing changes in aluminum concentration during a cycle test of a comparative example.
[0040] Figure 7 This is a graph showing changes in various properties in the cycle test of Comparative Examples.
[0041] Figure 8 This is a graph showing changes in various properties in the cycle test of Comparative Examples.
[0042] Fig. 9 This is a graph showing the relationship between the aluminum concentration and the etching amount in the cycle test of the comparative example.
[0043] Fig.10 This is a graph showing changes in aluminum concentration during cycle tests in Examples.
[0044] Fig.11 This is a graph showing changes in various properties in the cycle test of Examples.
[0045] Fig.12 This is a graph showing changes in various properties in the cycle test of Examples.
[0046] Fig.13 This is a graph showing changes in various properties (Ra and Rz values) in the cycle test of Examples. DETAILED DESCRIPTION
[0047] Embodiments of a method for producing an aluminum-resin composite (hereinafter referred to as a production method) and a surface treatment agent of the present invention will be described below.
[0048] The method for manufacturing an aluminum-resin composite of the present embodiment includes the following steps: a first surface treatment step, which is to contact the surface of the aluminum component with an alkaline surface treatment agent, which contains an alkali source, amphoteric metal ions, an oxidant, and a sulfur compound; a second surface treatment step, which is to contact the surface of the aluminum component after the aforementioned first surface treatment step with an acidic surface treatment agent, which contains halogen ions, aluminum ions, ammonium ions, and an acid, and contains an acid concentration of 3.0 mass % to 4.9 mass % of the aforementioned acid, and 0.2 mass % to 3.8 mass % of the aforementioned aluminum ions; and a bonding step, which is to bond the resin composition to the surface of the aluminum component after the aforementioned second surface treatment step.
[0049] [Aluminum-resin composite]
[0050] The production method of the present embodiment is a method of producing an aluminum-resin composite (hereinafter referred to as a “composite”) by bonding a resin composition to an aluminum member.
[0051] The composite may be an integrated aluminum member and a resin composition, and its use is not particularly limited. For example, it may be used as various machine parts such as electronic equipment parts, home appliance parts, and conveyor machine parts. More specifically, it may be used as various electronic equipment parts such as portable parts, home appliance parts, medical equipment parts, vehicle structural parts, vehicle-mounted parts, other electrical parts, or heat dissipation parts.
[0052] [First surface treatment step]
[0053] In the first surface treatment step, the surface of the aluminum member is brought into contact with an alkaline surface treatment agent containing an alkali source, amphoteric metal ions, an oxidizing agent, and a sulfur compound.
[0054] (Aluminum components)
[0055] The aluminum member refers to a member made of aluminum. The "aluminum" in the present embodiment may be made of aluminum or may be made of an aluminum alloy. Hereinafter, in this specification, "aluminum" refers to aluminum or an aluminum alloy.
[0056] The aluminum of this embodiment is not particularly limited, and examples thereof include alloys containing other metals such as Cu, Si, Fe, Mn, Mg, Zn, Ti, Ni, and Cr, pure aluminum, and aluminum containing impurities.
[0057] When the aluminum of the present embodiment is an alloy, there is no particular limitation on whether or not it is processed. For example, it may be unprocessed (F) after manufacturing, and as a tempered material, it may be annealed (O), work hardened (H), heat treated (T), etc. For example, it may be any tempered material of T3 tempering, T6 tempering, or T7 tempering.
[0058] In addition, the T3 tempered, T6 tempered, or T7 tempered material in the present embodiment refers to an alloy subjected to the respective tempers described in JIS H 0001 (Quality classification symbols of aluminum and aluminum alloys).
[0059] The shape of the aluminum member is not particularly limited. For example, aluminum blocks, plates, bars, etc. may be machined into a desired shape by plastic working, sawing, milling, electric discharge machining, drilling, pressing, grinding, polishing, etc., or by combining these processes.
[0060] The surface of the aluminum component bonded to the resin composition is preferably free of an oxide film or a thick film composed of no hydroxide, etc. In order to remove the thick film, the surface layer can be polished by mechanical polishing such as sandblasting, bead blasting, grinding, barrel processing, or chemical polishing before treatment with the surface treatment agent.
[0061] (Alkaline surface treatment agent)
[0062] The alkaline surface treatment agent of the present embodiment contains an alkali source, an amphoteric metal ion, an oxidizing agent, and a sulfur compound.
[0063] <Alkali source>
[0064] The alkali source is not particularly limited, and examples thereof include NaOH, KOH, etc. When NaOH or KOH is used as the alkali source, the hydroxide ion may be 0.60% by weight to 22.80% by weight, or 1.45% by weight to 16.30% by weight, or 2.50% by weight to 12.25% by weight, or 5.0% by weight to 9.3% by weight.
[0065] When the concentration of the hydroxide ion as the alkali source is within the above range, there are advantages in that a good roughened shape (dense concavo-convex shape) can be easily obtained and an appropriate roughening treatment rate can be obtained.
[0066] <Amphoteric Metal Ions>
[0067] The amphoteric metal ion is not particularly limited as long as it undergoes a substitution reaction with aluminum on the surface of the aluminum member.
[0068] Examples include amphoteric metal ions having an ionization tendency smaller than that of Al, and more specifically, Zn ions, Pb ions, Sn ions, Sb ions, Cd ions, etc. In particular, from the viewpoint of obtaining a good roughened shape suitable for improving the adhesion between the aluminum member and the resin composition and from the viewpoint of reducing the environmental load, Zn ions and Sn ions are more preferred, and Zn ions are more preferred.
[0069] The concentration of the amphoteric metal ion may be 0.2 mass % to 6.0 mass %, 0.5 mass % to 4.4 mass %, 1.0 mass % to 3.5 mass %, or 1.9 mass % to 3.5 mass %.
[0070] When the concentration of the amphoteric metal ion is within the above range, there are advantages in that a good roughened shape can be easily obtained and an appropriate roughening treatment speed can be obtained.
[0071] The amphoteric metal ion source is not particularly limited. For example, when it is a Zn ion source, zinc nitrate, zinc borate, zinc chloride, zinc sulfate, zinc bromide, basic zinc carbonate, zinc oxide, zinc sulfide, etc. are mentioned. In addition, when it is a Sn ion source, tin (IV) chloride, tin (II) chloride, tin (II) acetate, tin (II) bromide, tin (II) diphosphate, tin (II) oxalate, tin (II) oxide, tin (II) iodide, tin (II) sulfate, tin (IV) sulfide, tin (II) stearate, etc. are mentioned.
[0072] The amphoteric metal ions undergo a substitution reaction with aluminum on the surface of the aluminum member to precipitate an amphoteric metal on the surface of the aluminum member, and the amphoteric metal can be dissolved in the surface treatment agent again by the oxidizing agent described later. As described above, when the amphoteric metal is precipitated, it will dissolve in the liquid as its ions, and this step can be repeated to form a concave-convex shape suitable for improving the adhesion with the resin composition, that is, a roughened shape, on the surface of the aluminum member.
[0073] <Oxidant>
[0074] The oxidizing agent is not particularly limited as long as it can dissolve the above-mentioned amphoteric metal in the alkaline surface treatment agent. Examples thereof include chloric acid such as chlorous acid and hypochlorous acid and their salts, oxidizing metal salts such as permanganates, chromates, dichromates, and cerium (IV) salts, nitro-containing compounds, peroxides such as hydrogen peroxide and persulfates, nitric acid, and nitrate ions.
[0075] In particular, nitric acid and nitrate ions are more preferred from the viewpoint of easy handling.
[0076] When nitrate ions are used as the oxidizing agent, the source of nitrate ions is not particularly limited, and examples thereof include nitric acid, sodium nitrate, potassium nitrate, barium nitrate, calcium nitrate, ammonium nitrate, and zinc nitrate.
[0077] The concentration of the oxidizing agent may be, for example, 0.5 mass % to 10 mass %, 1.0 mass % to 8.4 mass %, or 2.0 mass % to 6.0 mass %.
[0078] When the concentration of the oxidizing agent is within the above range, there are advantages in that a good roughened shape can be easily obtained and an appropriate roughening treatment rate can be obtained.
[0079] <Sulfur compounds>
[0080] The alkaline surface treatment agent of the present embodiment contains a sulfur compound as a component that can form dense irregularities on the surface of the aluminum member and can further improve the airtightness or watertightness in the bonding interface of the composite.
[0081] The sulfur compound is not particularly limited as long as it can exert the above-mentioned effect, and examples thereof include one or more selected from thiosulfate ions and sulfur compounds having 1 to 7 carbon atoms. In particular, one or more selected from thiosulfate ions and sulfur compounds having 1 to 3 carbon atoms are more preferred.
[0082] In addition, thiosulfate ions can be contained in the surface treatment agent by blending an ion source thereof.
[0083] Examples of the sulfur compound having 1 to 7 carbon atoms include thiourea (carbon number 1), thioacetate ion (carbon number 2), thioacetic acid (carbon number 2), thioglycerol (carbon number 3), L-thioproline (carbon number 4), dithiodiacetic acid (carbon number 4), β,β'-thiodipropionic acid (carbon number 5), N,N-diethyldithiocarbamate ion (carbon number 5), 3,3'-dithiodipropionic acid (carbon number 6), 3,3'-dithiodipropanol (carbon number 6), o-thiocresol (carbon number 7), and p-thiocresol (carbon number 7).
[0084] The concentration of the sulfur compound may be 0.05% by mass to 25% by mass, 0.1% by mass to 20% by mass, or 0.2% by mass to 15% by mass.
[0085] When the concentration of the sulfur compound is within the above range, there are advantages in that a dense roughened shape is easily obtained and the air tightness or water tightness in the bonding interface of the composite is further improved.
[0086] <Other ingredients>
[0087] The alkaline surface treatment agent of this embodiment may optionally contain other additives. Other components may include hydroxycarboxylic acids such as citric acid, malic acid, gluconic acid, and salts thereof, additives for suppressing sludge generated by aluminum dissolution, surfactants for removing surface contaminants that cause uneven roughening, pH adjusters, and the like.
[0088] When these other components are added, the content thereof is more preferably 0.1 mass % or more and 5 mass % or less.
[0089] The pH of the alkaline surface treatment agent is not particularly limited, but may be in the range of pH 12 or more.
[0090] Alternatively, the alkaline surface treatment agent can be easily prepared by dissolving the aforementioned components in an appropriate solvent such as ion-exchanged water, pure water, or ultrapure water.
[0091] Unless otherwise specified, the components of the alkaline surface treatment agent may be used alone or in combination of two or more.
[0092] In the first surface treatment step, the method for bringing the surface treatment agent into contact with the surface of the aluminum member is not particularly limited, and the surface treatment can be carried out by publicly known methods. For example, treatment methods such as dipping and spraying can be used. The treatment temperature and treatment time can also be appropriately adjusted. For example, the treatment temperature is 25 to 45° C. and the treatment time is about 30 to 90 seconds.
[0093] [Second surface treatment step]
[0094] In the second surface treatment step, the surface of the aluminum component that has undergone the first surface treatment step is contacted with an acidic surface treatment agent, which contains halogen ions, aluminum ions, ammonium ions, and an acid, and contains the aforementioned acid at an acid concentration of not less than 3.0 mass % and not more than 4.9 mass %, and not less than 0.2 mass % and not more than 3.8 mass % of the aforementioned aluminum ions.
[0095] (Acidic surface treatment agent)
[0096] The surface treatment agent used in the second surface treatment step of this embodiment is a treatment agent composed of an acidic solution, and contains halogen ions, aluminum ions, ammonium ions, and acids, and contains the aforementioned acids at an acid concentration of not less than 3.0 mass % and not more than 4.9 mass %, and contains not less than 0.2 mass % and not more than 3.8 mass % of the aforementioned aluminum ions.
[0097] <Halogen ions>
[0098] The halogen ions have a function of controlling the surface shape of the aluminum member obtained in the first surface treatment step to a shape that can improve adhesion with the resin composition.
[0099] Examples of the concentration of halogen ions include 9.1 mass % to 35.2 mass %, 9.6 mass % to 31.6 mass %, and 10.0 mass % to 28.8 mass %.
[0100] When the concentration of the halogen ions is within the above range, there is an advantage that the shape can be easily controlled to improve the adhesion with the resin composition.
[0101] The halogen ion is not particularly limited, and examples thereof include at least one ion selected from the group consisting of a chloride ion, a bromide ion, and a fluoride ion.
[0102] The halogen ion source is not particularly limited, and examples thereof include halogenated hydrogen acids such as hydrochloric acid, aluminum chloride, sodium chloride, magnesium chloride, calcium chloride, ammonium chloride, ammonium bromide, ammonium fluoride, halogen compounds such as chloroacetic acid, and the like.
[0103] The halogen ion source may be a compound that can function as a supply source of aluminum ions, ammonium ions, or an acid described below in addition to being a halogen ion supply source.
[0104] <Aluminum ions>
[0105] Aluminum ions have a function of being controlled into a shape that can improve adhesion with the resin composition.
[0106] The aluminum ion concentration may be, for example, 0.20 mass % to 3.8 mass %, 0.25 mass % to 3.5 mass %, or 0.30 mass % to 3.3 mass %.
[0107] When the concentration of aluminum ions is within the above range, there is an advantage that the shape can be easily controlled to improve the adhesion with the resin composition.
[0108] The aluminum source is not particularly limited, and examples thereof include aluminum salts such as aluminum chloride, aluminum sulfate, aluminum oxide, aluminum nitrate, aluminum lactate, aluminum bromide, and aluminum metal (in the form of flakes or powder).
[0109] In addition, when aluminum chloride is used as the aluminum source, it can also function as a supply source of halogen ions such as chloride ions.
[0110] It is known that acidic liquids are generally highly reactive with respect to aluminum. Therefore, it is considered to adjust the reactivity by setting the aluminum concentration in the liquid to a higher level. However, if the aluminum component is continuously treated at this time, the aluminum concentration will be reduced due to the infiltration of the washing water into the surface treatment agent, etc., and the surface of the aluminum component cannot be adjusted to a more preferred shape. In addition, in order to adjust the aluminum concentration, it is also considered to treat while supplying aluminum ions, but in order to supply aluminum ions, it is necessary to supply a liquid that dissolves a high concentration of aluminum salt, which may increase the supply cost. In addition, due to the different infiltration amounts of washing water, it is difficult to keep the aluminum concentration fixed.
[0111] Therefore, the acidic surface treatment agent of the present embodiment is blended with relatively low concentrations of aluminum ions and ammonium ions described below, and further an amine compound or the like is added, thereby being able to stably adjust to a more preferred shape even in continuous treatment.
[0112] <Ammonium ion>
[0113] The ammonium ion has a function of controlling the shape to improve the adhesion with the resin composition.
[0114] Examples of the ammonium ion concentration include 0.033 mass % to 3.37 mass %, 0.10 mass % to 2.70 mass %, and 0.17 mass % to 1.68 mass %.
[0115] When the concentration of ammonium ions is within the above range, there is an advantage that the shape can be easily controlled to improve the adhesion with the resin composition.
[0116] The ammonium ion source is not particularly limited, and examples thereof include ammonium salts such as ammonium chloride, ammonium bromide, ammonium fluoride, methyl ammonium chloride, or quaternary alkyl ammonium salts such as dimethyl ammonium chloride, trimethyl ammonium chloride, and tetramethyl ammonium chloride.
[0117] In addition, when ammonium chloride is used as the ammonium source, it can also function as a supply source of halogen ions such as chloride ions.
[0118] <Amine compounds>
[0119] The acidic surface treatment agent of the present embodiment may contain an amine compound.
[0120] The amine compound has a function of being easily controlled into a shape that can improve adhesion with the resin composition.
[0121] Examples of the concentration of the amine compound include 0.05 mass % to 5.0 mass %, 0.10 mass % to 4.8 mass %, and 0.20 mass % to 4.5 mass %.
[0122] When the concentration of the amine compound is within the above range, there is an advantage that it is easy to continuously control the shape that can improve adhesion even when the treatment is continuous. In addition, when the concentration of the amine compound is within the above range, the etching performance with respect to the aluminum surface is good. Therefore, there is an advantage that even if a type of aluminum that is not easy to etch is used, an aluminum-resin composite with high bonding strength can be obtained.
[0123] The amine compound is not particularly limited and examples thereof include monovalent hydroxy alcohol compounds such as monoethanolamine, dimethylaminoethanol, diethylaminoethanol, methylaminoethanol, ethylaminoethanol, dimethylaminopropanol, methylaminopropanol, diethylaminopropanol, and butylaminobutanol; divalent hydroxy alcohol compounds such as diethanolamine, ethyldiethanolamine, and butyldiethanolamine; and trivalent hydroxy alcohol compounds such as triethanolamine.
[0124] In addition, examples of the amine compound include polyamine-based polymers such as polyallylamine and polyallylamine salts, and / or copolymers of hydrochlorides of these polymers, or diallylamine-based polymers such as diallylamine polymers, diallylamine salt polymers, diallylamine / sulfur dioxide copolymers, and diallylamine salt / sulfur dioxide copolymers, and / or copolymers of hydrochlorides of these polymers.
[0125] <Acid>
[0126] The acid has a function of controlling the shape to improve the adhesion with the resin composition.
[0127] The acid concentration may be, for example, 3.0 mass % to 4.9 mass % or 3.05 mass % to 4.5 mass %.
[0128] When the acid concentration is within the above range, there is an advantage that it is easy to continue to control the shape that can improve adhesion even during continuous treatment.
[0129] The acid is not particularly limited, and examples thereof include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, and hydrofluoric acid, and organic acids such as acetic acid and formic acid.
[0130] When hydrochloric acid is used as the acid, it can also function as a supply source of halogen ions such as chloride ions.
[0131] When hydrochloric acid is used as the acid, for example, when 35% hydrochloric acid is used, the acid concentration is contained in an amount of 8.5 mass % to 14.0 mass % or in an amount of 8.7 mass % to 12.85 mass % to fall within the above-mentioned acid concentration range.
[0132] As a component of the acidic surface treatment agent of this embodiment which can supply the halogen ion source and each of the above-mentioned components simultaneously, the acidic surface treatment agent contains hydrochloric acid, aluminum chloride, and ammonium chloride, for example.
[0133] That is, the acidic surface treatment agent containing this component contains aluminum chloride as a supply source of halogen ions and aluminum ions, ammonium chloride as a supply source of halogen ions and ammonium ions, and hydrochloric acid as a supply source of halogen ions and acid.
[0134] <Other ingredients>
[0135] The acidic surface treatment agent of this embodiment may optionally contain other additives.
[0136] Examples of other components include pH adjusters, metal ions or metal compounds such as copper ions and iron ions, and oxidants such as sodium persulfate, sodium perchlorate, nitric acid, and potassium nitrate.
[0137] When these other components are added, the content thereof is more preferably about 0.05 mass % or more and 5.0 mass % or less.
[0138] The acidic surface treatment agent can be easily prepared by dissolving the above-mentioned components in an appropriate solvent such as ion-exchanged water, pure water, or ultrapure water.
[0139] The pH of the acidic surface treatment agent is not particularly limited, but may be in the range of pH 2 or less.
[0140] Unless otherwise specified, the components of the acidic surface treatment agent may be used alone or in combination of two or more.
[0141] The acidic surface treatment agent of the present embodiment contacts the surface of the aluminum member to chemically etch the aluminum, thereby roughening the aluminum.
[0142] That is, without using electricity such as electrolytic etching, fine irregularities are formed (roughened) on the surface of the aluminum member by chemical etching.
[0143] In the second surface treatment step, the method of bringing the acidic surface treatment agent into contact with the surface of the aluminum member is not particularly limited, and the treatment can be carried out by publicly known methods. For example, treatment methods such as immersion and spraying can be used. The treatment temperature and treatment time can also be appropriately adjusted. For example, the treatment temperature is 25 to 40° C. and the treatment time is about 30 to 600 seconds.
[0144] In the second surface treatment step, when the treatment is continued, the concentration of each component can be used as a management index, and additives can be appropriately added within a fixed range.
[0145] For example, when the acid concentration is used as a management index, the acid concentration may be maintained in the range of 3.0 mass % to 4.9 mass %, or in the range of 3.1 mass % to 4.5 mass %.
[0146] When the aluminum ion concentration is used as a management index, it can be maintained in a range of 0.2 mass % to 3.8 mass %, 0.25 mass % to 3.5 mass %, or 0.30 mass % to 3.3 mass %.
[0147] By maintaining the acid concentration and / or the aluminum ion concentration within the above range, the performance of the acidic surface treatment agent can be maintained, and the surface of the aluminum member can be made into an appropriate surface shape in which the bonding strength with the resin composition is sufficiently increased.
[0148] In order to maintain the concentration range of each component according to the above-mentioned management index, a process of adding appropriate additives at appropriate times is performed.
[0149] As additives, an acid component is added when the acid concentration is used as a management index, and an aluminum ion source is added when the aluminum ion concentration is used as a management index. In this case, individual components may be added alone, or a mixed component of the components may be added.
[0150] The surface of the aluminum member after the second surface treatment step can have the following surface shapes, for example.
[0151] That is, the arithmetic mean roughness (Ra) can be 0.5 μm to 3.0 μm, or 1.1 μm to 3.0 μm, or 1.1 μm to 2.5 μm, and the ten-point average roughness (Rz) can be 8 μm to 30 μm, or 10 μm to 30 μm, or 10 μm to 25 μm.
[0152] By setting it as the above-mentioned surface shape, the bonding strength of the obtained aluminum-resin composite can be sufficiently improved.
[0153] In the method of this embodiment, even if the second surface treatment step is repeatedly and continuously performed, the surface shape of the aluminum member after the second surface treatment step can be maintained as the above-mentioned surface shape.
[0154] The numerical values of the arithmetic mean roughness (Ra) and the ten-point mean roughness (Rz) mentioned above refer to the case where the average value of three or more measurements of each sample falls within the above numerical range.
[0155] [Washing steps]
[0156] The manufacturing method of this embodiment includes a cleaning step of ultrasonically cleaning the surface of the aluminum member after the second surface treatment step.
[0157] In the washing step, the treatment conditions of ultrasonic washing are not particularly limited, and for example, ultrasonic treatment may be performed at a treatment temperature of 25° C. to 60° C. for 3 to 15 minutes and a frequency of 25 kHz to 120 kHz, preferably 40 kHz to 80 kHz. The ultrasonic treatment may be repeated multiple times.
[0158] This washing can remove the insoluble components (aluminum stain layer) present on the surface of the aluminum component after the first and second surface treatment steps, so that the adhesion between the aluminum component and the resin composition after subsequent joining can be good and high joining strength can be obtained.
[0159] In the washing step, the ultrasonic washing may be performed after the surface of the aluminum member is brought into contact with an aqueous nitric acid solution having an acid concentration of 10.0 mass % or more and 50.0 mass % or less.
[0160] Although contact with the aqueous nitric acid solution is not essential, the cleaning effect of ultrasonic cleaning can be further improved by performing such contact treatment.
[0161] The method of contacting with the nitric acid aqueous solution is not particularly limited, and the contact may be made by publicly known methods. Examples include methods such as immersion and spraying. The treatment temperature and treatment time may also be appropriately adjusted. Examples include a treatment temperature of 25 to 35° C. and a treatment time of about 30 to 60 seconds.
[0162] [Other steps]
[0163] In the method of this embodiment, more steps may be arbitrarily included before and after each step.
[0164] For example, a washing step with water or other washing liquid, or a drying step of the treated surface can be performed after each step, thereby further improving the treatment effect of each step.
[0165] [Joining steps]
[0166] The method of the present embodiment includes a bonding step of bonding the resin composition to the surface of the aluminum member that has been subjected to the aforementioned washing step.
[0167] (Resin composition)
[0168] The resin composition used in this embodiment is not particularly limited as long as it can be bonded to aluminum components, and examples thereof include PPS (polyphenylene sulfide) resin, liquid crystal polymer, polyamide-imide resin, polyimide resin, polyamide resin, PEEK (polyetheretherketone) resin, PBT (polybutylene terephthalate) resin, epoxy resin, ETFE (tetrafluoroethylene / ethylene copolymer) resin, PFA (tetrafluoroethylene / perfluoroalkyl vinyl ether copolymer) resin, or PTFE (polytetrafluoroethylene) resin.
[0169] The method for bonding the resin composition to the surface of the aluminum component in the bonding step is not particularly limited, and examples thereof include a coating method in which the resin composition is dissolved or dispersed in a solvent and then applied, or a method in which the resin composition is bonded to the surface of the aluminum component by injection molding.
[0170] The conditions for bonding the resin composition and the aluminum member to each other can be appropriately set to publicly known conditions.
[0171] For example, the expected bonding strength varies depending on the type of resin, and therefore it is more preferable to set bonding conditions that can obtain the required bonding strength according to the type of resin.
[0172] The composite body produced by the method for producing an aluminum-resin composite body according to the present embodiment can obtain high bonding strength.
[0173] In addition, in the method for producing the aluminum-resin composite of the present embodiment, the aluminum-resin composite having the above-mentioned high bonding strength can be obtained even when aluminum members are continuously processed.
[0174] The acidic surface treatment agent of the present embodiment can be used as a surface treatment agent for chemically etching the surface of an aluminum member (hereinafter referred to as a chemical surface treatment agent) in a method other than the production method of the present embodiment described above.
[0175] In this case, before treatment with the surface treatment agent, the surface of the aluminum component may be roughened to a desired degree by other methods (mechanical polishing method, chemical polishing method, etc.).
[0176] The chemical surface treatment agent of the present embodiment can further adjust the fine irregularities of the aluminum surface, thereby forming a surface shape that can improve adhesion with the resin composition.
[0177] For example, by mechanical grinding or chemical grinding performed using a publicly known aluminum roughening agent, an aluminum component having fine irregularities on its surface is treated with the chemical surface treatment agent of this embodiment, thereby obtaining an aluminum component having a surface shape with an arithmetic mean roughness (Ra) of 0.5 μm to 3.0 μm, or 1.1 μm to 3.0 μm, or 1.1 μm to 2.5 μm, and a ten-point average roughness (Rz) of 8 μm to 30 μm, or 10 μm to 30 μm, or 10 μm to 25 μm.
[0178] The above-mentioned surface shape can be used for applications that can utilize the roughened shape of the surface of the treated aluminum member, for example, applications in bonding resin compositions.
[0179] In addition, the aluminum constituting the aluminum member generally has differences in roughening ease or roughening shape after surface treatment due to differences in manufacturing method, composition, batch, etc. By performing the surface treatment of the method for manufacturing the aluminum-resin composite of this embodiment, a surface shape that can improve the adhesion with the resin composition can be formed according to the type of aluminum member, so various aluminum members can be used.
[0180] Although the method for producing the aluminum-resin composite and the surface treatment agent of the present embodiment are described above, it should be understood that the disclosed embodiments are illustrative in all aspects and are not intended to be limiting. The scope of the present invention is represented by the scope of the claims rather than the above description, and includes the equivalent meaning of the scope of the claims and all changes within the scope.
[0181] Example
[0182] The present invention will be described in more detail below with reference to Examples, but the present invention is not limited to these Examples.
[0183] [Test 1: Strength test]
[0184] (Surface treatment agent)
[0185] The alkaline surface treatment agent and the acidic surface treatment agent used in this example were prepared.
[0186] Each surface treatment agent is an aqueous solution prepared by dissolving the following materials in ion-exchanged water so as to have the concentration of each component shown in Table 1 (also shown as an ion concentration conversion value or an acid concentration conversion value).
[0187] Sodium hydroxide: reagent manufactured by KISHIDA CHEMICAL (special grade).
[0188] Zinc nitrate hexahydrate: reagent manufactured by KISHIDA CHEMICAL (grade one).
[0189] Sodium thiosulfate pentahydrate: reagent manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd. (special grade).
[0190] 35% hydrochloric acid: reagent manufactured by KISHIDA CHEMICAL (special grade).
[0191] Aluminum chloride hexahydrate: reagent manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd. (special grade).
[0192] Ammonium chloride: reagent manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd. (special grade).
[0193] Monoethanolamine: a reagent manufactured by Sigma-Aldrich (special grade).
[0194] In addition, the pH of the alkaline surface treatment agent used in the Examples and Comparative Examples was 12 or more, and the pH of the acidic surface treatment agent was 2 or less.
[0195] [Table 1]
[0196]
[0197] (Aluminum components)
[0198] As samples, members containing the following alloys having the compositions described in Table 2 were prepared.
[0199] In addition, as the alloy for components, alloys of the same alloy but of different batches (alloy batches 1 and 2) were used.
[0200] Al-Si alloy (A4032FH-T6): T6 quenched and tempered material for free forging (FH)
[0201] [Table 2]
[0202]
[0203] (Resin composition)
[0204] A PPS resin (1135MF1, manufactured by Polyplastics Corporation) was prepared as a resin composition.
[0205] (Etching amount)
[0206] The etching amount of each aluminum member is a value calculated by the following method and is shown in μm.
[0207] Etching amount = mass difference before and after treatment ÷ specific gravity of aluminum ÷ treated surface area.
[0208] Quality difference before and after treatment: The quality difference of each aluminum component was measured before the first surface treatment step and after the washing step.
[0209] Specific gravity of aluminum: 2.7.
[0210] Treatment surface area: The surface area of the aluminum component.
[0211] The etching amount is the result of measurement after treatment with the alkaline surface treatment agent and the acidic surface treatment agent, and is therefore the total etching amount of both treatments.
[0212] (Tensile shear strength)
[0213] The following treatments were performed on each aluminum member using each surface treatment agent.
[0214] Immerse in an alkaline surface treatment agent at 35°C for 1 minute, then rinse with water. Further immerse with the acidic surface treatment agent of the embodiment and comparative example at the temperature and treatment time shown in Table 3. Further rinse with water at room temperature for 0.5 minute, and immerse in a 15% nitric acid aqueous solution at room temperature for 0.5 minute. Then, ultrasonically clean with an ultrasonic cleaning device (device used: model CPX-2800H-J, manufactured by Yamato Scientific Co., Ltd., conditions: frequency 40kHz, room temperature) for 2 to 3 minutes, further rinse with water at room temperature for 0.5 minute, and then dry with a dryer.
[0215] In addition, the treatment time of the second surface treatment step is appropriately adjusted so as to achieve an appropriate roughening state (etching amount).
[0216] In addition, after the above treatment, an aluminum-resin composite body of a test piece was obtained by injection molding under the following molding conditions (apparatus used: model STX20S2V, Nissei Plastic Industry).
[0217] like Figure 1 As shown, a resin sheet with a length of 45 mm, a width of 10 mm, and a thickness of 3 mm is set on one side of the 18 mm side of a rectangular aluminum plate with a side of 45 mm, a width of 18 mm, and a thickness of 1.5 mm in such a way that the overlapping portion is 5 mm×10 mm, and an aluminum-resin composite is formed in this state.
[0218] Molding conditions
[0219] Cylinder temperature: 290℃.
[0220] Mould temperature: 160℃.
[0221] Theoretical injection volume: 66cm 3 / Second.
[0222] Injection pressure: 74Mpa.
[0223] Injection speed: 120mm / s.
[0224] Screw speed: 84rpm.
[0225] Maintaining pressure: 74MPa.
[0226] Cooldown: 20 seconds.
[0227] The test piece was stretched at a rate of 10 mm / min using a tensile testing machine (equipment used: precision universal testing machine AG-20kNXDplus, manufactured by Shimadzu Corporation). Figure 2 The test results are shown in Table 3.
[0228] (Surface roughness)
[0229] The surface roughness of each aluminum member treated with the acidic surface treatment agent was measured by the following method.
[0230] Determination method of arithmetic mean roughness (Ra) and ten-point average roughness (Rz):
[0231] The arithmetic mean roughness (Ra) and the ten-point average roughness (Rz) were measured using a non-contact confocal laser microscope. The measurement was performed using a laser microscope (device used: model OPTELICS HYBLID+, manufactured by Lasertec) using a 50x objective lens. The surface roughness was measured in accordance with the contact standard (JIS B 0633: 2001). The arithmetic mean roughness (Ra) and the ten-point average roughness (Rz) were measured three times for each sample, and the individual average values were calculated.
[0232] The results are shown in Table 3.
[0233] [Table 3]
[0234]
[0235] The tensile shear strength of the methods of the examples all exceeded 15 MPa. In addition, the values of surface roughness (arithmetic mean roughness (Ra) and ten-point mean roughness (Rz)) were higher than those of the comparative examples.
[0236] [Test 2: Cycle Test 1]
[0237] The surface treatment agents shown in Table 4 were prepared.
[0238] [Table 4]
[0239]
[0240] An aluminum member (aluminum alloy ADC12) having a length and width of 40 mm×40 mm and a thickness of 2 mm was prepared as a test substrate. Table 5 shows the composition of the aluminum alloy ADC12.
[0241] [Table 5]
[0242]
[0243] The test substrates were processed successively in the following manner.
[0244] Prepare 1 L of each of the alkaline surface treatment agent and the acidic surface treatment agent.
[0245] The test substrate was first immersed in an alkaline surface treatment agent at 35°C for 1 minute and then washed with water. Then, it was immersed in an acidic surface treatment agent at 35°C for 1 minute and 30 seconds, and then further washed with water at room temperature for 0.5 minutes, and immersed in a 15% nitric acid aqueous solution at room temperature for 0.5 minutes. Then, it was ultrasonically washed for 2 to 3 minutes using an ultrasonic washing device (device used: model CPX-2800H-J, manufactured by Yamato Scientific Co., Ltd., conditions: frequency 40kHz, room temperature), and then further washed with water at room temperature for 0.5 minutes, and then dried in a dryer.
[0246] Four test substrates were treated in each batch under the treatment conditions. The amount of water used to infiltrate the acidic surface treatment agent and the amount of the surface treatment agent removed were adjusted to 10 mL each for each batch of washing water. The acid concentration was measured every 8 batches. If the acid concentration reached 0.9 mol / L, 34 ml of 35% hydrochloric acid was added (or the acid concentration was 1.25 mol / L). The etching amount of the test substrates before and after the addition of hydrochloric acid (2 batches), the surface roughness of each test substrate, and the tensile shear strength were measured.
[0247] The aluminum concentration was measured every 16 batches. The measurement was performed using an atomic absorption spectrophotometer (apparatus used: Model AA-7000, manufactured by Shimadzu Corporation).
[0248] In addition, if the treatment is continued, the components in the acidic surface treatment agent will be diluted due to the infiltration of washing water and the adjustment of acid concentration. Therefore, ammonium chloride and monoethanolamine were added every 32 batches to return them to the blending amount before the treatment.
[0249] The cycle test was carried out until 161 batches (treatment area 2.0m 2 / L).
[0250] The etching amount and surface roughness were measured in the same manner as in Test 1.
[0251] In addition, after the cycle test was completed (after 161 batches), aluminum-resin composite test pieces were prepared in the same manner as in Test 1 using processed substrates (4 pieces x 2 batches) of each target batch, and the tensile shear strength was measured.
[0252] In addition, all substrates except those used in each measurement were reused.
[0253] The results are shown in Figures 3 to 5of charts.
[0254] like Figures 3 to 5 As shown in the graph, all measured values remain stable. Figure 3 As shown in Figure 2, the aluminum concentration was stable during the treatment (the aluminum concentration was 9.7 to 13.0 g / L, which was 0.9 to 1.2 mass % in terms of mass %). Figure 4 As shown in the figure, it can be seen that the etching amount and acid concentration are both stable (etching amount is 7.0 to 9.7 μm, acid concentration is 0.94 to 1.25 mol / L, and mass % is 3.2 to 4.3 mass %), and the tensile shear strength is stable even if the treatment is continued, and good results can be obtained. Figure 5 As shown, it can be seen that the acid concentration is maintained between 0.9 mol / L (3.1 mass % in terms of mass %) and 1.25 mol / L (4.3 mass % in terms of mass %), and thus the surface roughness can be maintained within a good range (arithmetic mean roughness (Ra) of 1.33 μm to 1.85 μm, ten-point average roughness (Rz) = 12.9 μm to 16.9 μm) through treatment. From this, it can be seen that the components other than the aluminum concentration and the acid concentration are always in a stable state.
[0255] [Test 3: Changes in component concentration 1]
[0256] The component concentrations of the acidic surface treatment liquid were set to the concentrations shown in Table 6, and the etching amount, tensile shear strength and surface roughness were measured in the same manner as in the above-mentioned Test 1. In addition, the halogen ions in Table 6 are chloride ions.
[0257] In addition, the substrate used in Test 2 (composed of the alloy described in Table 5) was used as the test substrate.
[0258] The results are shown in Table 6.
[0259] [Table 6]
[0260]
[0261] As shown in Table 6, the etching amount, tensile shear strength and surface roughness in the examples were all good compared to the comparative examples.
[0262] [Test 4: Changes in component concentration 2]
[0263] The component concentrations of the acidic surface treatment liquid were set to the concentrations shown in Table 7, and the etching amount, tensile shear strength, and surface roughness were measured in the same manner as in the above-mentioned Test 1.
[0264] The alkaline surface treatment agent used was the same as that used in Test 1, and the components of the acidic surface treatment agent used were as follows. The test substrate used was the same as that used in Test 2.
[0265] 35% hydrochloric acid: reagent manufactured by KISHIDA CHEMICAL (special grade).
[0266] Ammonium ion source: ammonium chloride, reagent (special grade) manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.
[0267] Aluminum ion source: aluminum chloride hexahydrate, reagent (special grade) manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.
[0268] Polyallylamine polymer: manufactured by Sigma-Aldrich Co., trade name: polyallylamine solution.
[0269] Triethanolamine: reagent manufactured by Sigma-Aldrich (special grade).
[0270] Monoethanolamine: a reagent manufactured by Sigma-Aldrich (special grade).
[0271] Bromide ion source: ammonium bromide, reagent (special grade) manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.
[0272] The results are shown in Table 7.
[0273] [Table 7]
[0274]
[0275] As shown in Table 7, even when the type of the amine compound was changed or when no amine compound was contained, the etching amount, tensile shear strength, and surface roughness were all good.
[0276] [Test 5: Cycle Test 2]
[0277] The surface treatment agent shown in Table 8 (containing no ammonium ions or amine compounds and having an aluminum concentration higher than that in Test 2) was prepared as an acidic surface treatment agent. The alkaline surface treatment agent used was the same as that used in Test 2. The test substrate used was also the same as that used in Test 2.
[0278] [Table 8]
[0279]
[0280] The cycle test was carried out in the same manner as in Test 2, except that ammonium chloride and monoethanolamine were not added midway, until 129 batches (treatment area of 1.6512 m 2 / L). The results are shown in Figures 6 to 9 of charts.
[0281] like Figures 6 to 9 As shown in the graph, the measured values are not stable compared to Test 2.
[0282] The acidic surface treatment agent in this test does not contain ammonium ions and amine compounds, so the aluminum concentration is set high in order to obtain a certain etching amount. Figure 6 As shown, if the treated area increases, the aluminum concentration will decrease, e.g. Figure 7 As shown in Figure 2, as the processing area increases, the etching amount decreases. Figure 8 As shown in Figure 2, the tensile shear strength will also decrease with the increase of the treated area. If the treated area exceeds 0.5m 2 It will be significantly reduced if it exceeds 1.0m 2 The result will be lower than 35MPa.
[0283] As described above, it is understood that when an acidic surface treatment without ammonium ions and amine compounds is used, stable treatment cannot be performed and the tensile shear strength is also low.
[0284] [Test 6: Cycle Test 3]
[0285] As the acidic surface treatment agent, each surface treatment agent (containing no amine compound) shown in Table 9 was prepared. As the alkaline surface treatment agent, the same alkaline surface treatment agent as in Test 2 was used. As the test substrate, the same test substrate as in Test 2 was also used.
[0286] [Table 9]
[0287]
[0288] The cycle test was carried out in the same manner as in Test 2, except that monoethanolamine was not added midway, until 117 batches (treatment area of 1.4976 m 2 / L).
[0289] The results are shown in Figures 10 to 13 of charts.
[0290] like Figures 10 to 13 As shown in the graph, each measured value is more stable than that in Test 5.
[0291] On the other hand, the etching amount was slightly smaller than the result of Test 2, and the numerical values of the surface roughness tended to be lower overall.
Claims
1. A method for producing an aluminum-resin composite, comprising the following steps: The first surface treatment step is to contact the surface of the aluminum component with an alkaline surface treatment agent, wherein the alkaline surface treatment agent contains an alkali source, amphoteric metal ions, an oxidant, and a sulfur compound; a second surface treatment step of contacting the surface of the aluminum member after the first surface treatment step with an acidic surface treatment agent, wherein the acidic surface treatment agent contains halogen ions, aluminum ions, ammonium ions, and an acid, and contains the acid at an acid concentration of 3.0 mass % to 4.9 mass % and the aluminum ions at 0.2 mass % to 3.8 mass %; and The bonding step is to bond the resin composition to the surface of the aluminum member that has been subjected to the second surface treatment step.
2. The method for producing an aluminum-resin composite according to claim 1, wherein the acidic surface treatment agent contains an amine compound. 3 . The method for producing an aluminum-resin composite according to claim 2 , wherein the acidic surface treatment agent contains 0.05 mass % or more and 5.0 mass % or less of the amine compound. 4 . The method for producing an aluminum-resin composite according to claim 1 , wherein the acidic surface treatment agent contains the ammonium ion in an amount of 0.033 mass % to 3.37 mass %.
5. The method for producing an aluminum-resin composite according to claim 1, wherein the halogen ion is at least one selected from the group consisting of chloride ion, bromide ion, and fluoride ion.
6. The method for producing an aluminum-resin composite according to claim 1, wherein the acidic surface treatment agent contains hydrochloric acid, aluminum chloride, and ammonium chloride.
7. The method for producing an aluminum-resin composite according to claim 1, wherein the sulfur compound of the basic surface treatment agent is at least one selected from thiosulfate ions and sulfur compounds having 1 to 7 carbon atoms.
8. The method for producing an aluminum-resin composite according to claim 1, further comprising the following steps: In the cleaning step, the surface of the aluminum member after the second surface treatment step is ultrasonically cleaned.
9. The method for producing an aluminum-resin composite according to claim 1, wherein in the second surface treatment step, the acid concentration of the acidic surface treatment agent is maintained in a range of 3.0 mass % to 4.9 mass %.
10. The method for producing an aluminum-resin composite according to claim 1, wherein in the second surface treatment step, the aluminum ion concentration of the acidic surface treatment agent is maintained in a range of 0.2 mass % to 3.8 mass %.
11. The method for producing an aluminum-resin composite according to claim 1, wherein the surface of the aluminum member subjected to the second surface treatment step has an arithmetic mean roughness (Ra) of 0.5 μm to 3.0 μm, and a ten-point average roughness (Rz) of 8 μm to 30 μm.
12. A surface treatment agent is an acidic solution, which contains halogen ions, an acid with an acid concentration of 3.0 mass % to 4.9 mass %, aluminum ions of 0.2 mass % to 3.8 mass %, and ammonium ions of 0.033 mass % to 3.37 mass %, and the acidic solution contains halogen ions, an acid with an acid concentration of 3.0 mass % to 4.9 mass %, an aluminum ion of 0.2 mass % to 3.8 mass %, and an ammonium ion of 0.033 mass % to 3.37 mass %, and the acidic solution roughens the aluminum by chemically etching the surface of the aluminum component by contact with the surface of the aluminum component. 13 . The surface treatment agent according to claim 12 , wherein the acidic solution contains 0.05 mass % or more and 5.0 mass % or less of the amine compound.
14. The surface treatment agent according to claim 12, wherein the halogen ion is at least one selected from the group consisting of chloride ion, bromide ion, and fluoride ion.
15. The surface treatment agent according to claim 12, wherein the acidic solution contains hydrochloric acid, aluminum chloride, and ammonium chloride.
Citation Information
Patent Citations
Surface roughening agent for aluminum and surface roughening method using the same
JP2011195949A
Method for producing aluminum-resin composite
JP2013052671A